Pengelolaan Keuangan Mandiri Sebagai Alat Manajemen Kebutuhan Rumah Tangga - Refni Sukmadewi; Setiawati; Elis Nurhanida (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Rising prices of basic necessities are often a problem for families with low or limited incomes. This condition is experienced by mothers who work as Outdoor Cleaning Service staff at the Engineering Service Unit (ESU) of the University of Riau. This service activity method is carried out by counseling about independent household financial management which is expected to help with the problems faced. The purpose of this activity is to assist the community in managing household finances to realize financial management in the future. This activity ran smoothly and received a fairly positive response from the Outdoor Cleaning Service staff at the Engineering Service Unit (ESU) at the University of Riau so that they could increase their knowledge and skills in managing finances better.